Moving from Feedback to Feedforward in IBDP classrooms. (August 2021) - Dulfer, Nicky; Akhlaghi Koopaei, Firoozeh
There is widespread acceptance of the positive impact of constructive feedback on students' learning progress. However, few studies investigate the role of feedforward in high-stakes learning environments. This research explores feedback and feedforward practices in International Baccalaureate Diploma Programme classrooms in Hong Kong and Australia. The article analyses 18 teachers' practices and perceptions about feedback and feedforward. The teachers' perceptions on feedforward were analysed using a survey and semi-structured interviews, while their teaching practices were evaluated using a lesson observation instrument. Results indicated that participants were aware of the importance of providing feedforward techniques and tools in the classroom to support students in closing the gaps between their current performance and desired performance. Not all teachers, however, incorporated feedforward in all their lessons as a learning tool or differentiation strategy to enhance students' learning experience and assessment outcomes.